Indonesian Rheumatology Association (IRA) Recommendations for Diagnosis and Management of Sjogren’s Syndrome - Deddy Nur Wachid Achadiono (Indonesian Journal of Rheumatology, 2023)
Background. Sjogren’s syndrome (SS) is a systemic autoimmune diseasethat affects exocrine glands. Dealing with SS is challenging due to the lowlevel of awareness and knowledge about SS, as well as the difficulty indiagnosing and treating the disease. Diagnosing SS requires manysupporting examinations from many medical specialties. Therefore, theserecommendations were developed to serve as a guide for health practitionersin diagnosing and treating SS. Methods. Six selected rheumatologists fromthe Indonesian Rheumatologist Association (IRA) formulated therecommendations based on key questions formed by a steering committeefrom IRA. These recommendation materials were taken from several onlinedatabases such as PubMed, Science Direct, and Google Scholar. Level of evidence and grades of recommendation were then assigned, and everymember of the panellist team will assign a score for level of agreement.Results. The panel generated a total of 19 recommendations discussing thediagnosis, pharmacological and non-pharmacological therapy, andprognosis for SS. Conclusion. These recommendations can be used to helpclinicians correctly diagnose and choose the most suitable therapy for SSpatients. All recommendation statements were created with theconsideration of Indonesia’s clinical setting, facility, and drug availability.